2017
DOI: 10.1007/s00018-017-2720-9
|View full text |Cite
|
Sign up to set email alerts
|

Blockage of the NLRP3 inflammasome by MCC950 improves anti-tumor immune responses in head and neck squamous cell carcinoma

Abstract: The NLRP3 inflammasome is a critical innate immune pathway responsible for producing active interleukin (IL)-1β, which is associated with tumor development and immunity. However, the mechanisms regulating the inflammatory microenvironment, tumorigenesis and tumor immunity are unclear. Herein, we show that the NLRP3 inflammasome was over-expressed in human HNSCC tissues and that the IL-1β concentration was increased in the peripheral blood of HNSCC patients. Additionally, elevated NLRP3 inflammasome levels were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(85 citation statements)
references
References 55 publications
2
83
0
Order By: Relevance
“…In agreement, in a mouse breast cancer model inhibition of NLRP3 effectively reduced the tumor-resident population of MDCS [288] and TAM [232]. Similarly, in a HNSCC mouse model, a reduction of MDSC, Treg and TAM frequencies was achieved by blocking NLRP3 inflammasome activation using the specific inhibitor MCC950 [226]. Comparable effects were observed in murine and human breast cancer models when applying Anakinra.…”
Section: Inhibition Of Il-1 Signaling Inhibits Tumor Growthmentioning
confidence: 83%
See 1 more Smart Citation
“…In agreement, in a mouse breast cancer model inhibition of NLRP3 effectively reduced the tumor-resident population of MDCS [288] and TAM [232]. Similarly, in a HNSCC mouse model, a reduction of MDSC, Treg and TAM frequencies was achieved by blocking NLRP3 inflammasome activation using the specific inhibitor MCC950 [226]. Comparable effects were observed in murine and human breast cancer models when applying Anakinra.…”
Section: Inhibition Of Il-1 Signaling Inhibits Tumor Growthmentioning
confidence: 83%
“…In addition, Treg and carcinoma-associated fibroblasts (CAF) contribute to the immunosuppressive milieu [222,223,224,225]. In a head and neck squamous cell carcinoma (HNSCC) mouse model inflammasome activation and thereby IL-1β upregulation was shown to cause an insufficient anti-tumor reactivity via the immunosuppressive network of MDSC, TAM and Treg [226]. MDSC and Treg have also been illustrated to be key negative regulators of the immune system in melanoma patients [227,228,229].…”
Section: Role Of Il-1β In Tumor Developmentmentioning
confidence: 99%
“…Several specific inhibitors, such as MCC950, CY‐09, arglabin, and glyburide, have been recently developed or identified to target NLRP3 inflammasome inhibition . The application of these specific NLRP3 inflammasome inhibitors has demonstrated therapeutic effects in various inflammatory disease mouse models, including models of myocardial infarction, fulminant hepatitis, steatohepatitis, lupus nephritis, atherosclerosis, Alzheimer's disease, brain injury, inflammatory bowel diseases, acute colitis, and carcinoma In allergic diseases, the application of MCC950 reduces skin and airway inflammation in mouse models of allergic dermatitis and asthma . More recently, 2 studies have shown that the targeted inhibition of NLRP3 inflammasomes with a specific inhibitor decreased IL‐1β and TH2 cytokines and inhibited HDM‐induced AHR and steroid‐resistant asthma in a mouse model .…”
Section: Discussionmentioning
confidence: 99%
“…However, these cells secrete biologically active IL-1β in an autonomous way without the presence of exogenous stimuli at late stages of the disease ( 54 ). In HNSCC, NLRP3 inflammasome is found upregulated in carcinoma tissues and associated with carcinogenesis and cancer stem cells (CSCs) self-renewal activation ( 46 48 ). Also, NLRP3 signaling seems to drive immunosuppression in pancreatic carcinoma, by promoting tolerogenic T cell differentiation and adaptive immune suppression via IL-10 ( 56 ).…”
Section: Nlrp3 Inflammasomementioning
confidence: 99%